Analisis Kapasitas Ruang Parkir Off Street Sepeda Motor dan Mobil di Ruko Mega Galaxy Surabaya - Muhammad Satria Wicaksono; Zainal Abidin; Miftachul Huda (AGREGAT, 2019)
Abstract Parking is one of the elements that cannot be separated from the overall road transportation system. The existence of infrastructure such as parking facilities is urgently needed, one of which is in offices. The availability of parking spaces is often not able to accommodate vehicles so there is a need to analyze the capacity of parking spaces. The case study location was taken at Ruko Mega Galaxy Surabaya. In analyzing the parking space capacity, we will discuss the conditions of parking spaces, characteristics of parking spaces, and problem solving. The discussion on this problem starts from the identification of problems in the field, literature studies, preliminary surveys to determine the existing conditions and data collection. Then proceed with analyzing the data and discussion, so that the actual parking space capacity obtained on motorbikes and cars. Furthermore, characteristic analysis is applied according to Director General of Land Transportation 1996, then conclusions and recommendations are drawn. From the results of this survey, the parking characteristics of Ruko Mega Galaxy Surabaya, namely the static capacity of vehicles as much as 500 SRP motorcycles and 120 SRP cars. On the maximum accumulation of 556 motorbike parking lots and 138 vehicles. The volume of motorcycle parking is 1256 vehicles and cars are 941 vehicles. For maximum motorcycle parking duration 3.69 hours and 2.07 hours car. Turn over the maximum parking of motorbikes 3 times change and car 8 times change. The maximum motorcycle parking index is 111% and cars are 115%. and dynamic motorbike capacity of 2300 SRP and 552 SRP cars. Based on factual conditions, the maximum accumulation of parking has not been able to accommodate the volume of vehicles so that if it is projected in the next 3 years SRP is needed. Keywords: Characteristics, SRP, Motorcycle, Car, ShophouseAbstrakParkir merupakan salah satu unsur sarana yang tidak dapat dipisahkan dari sistem transportasi jalan raya secara keseluruhan. Keberadaan prasarana seperti fasilitas parkir sangat dibutuhkan salah satunya di perkantoran. Ketersediaan ruang parkir sering kali tidak mampu menampung kendaraan sehingga perlu adanya analisis terhadap kapasitas ruang parkir. Lokasi studi kasus ini diambil di Ruko Mega Galaxy Surabaya .Dalam melakukan analisis kapasitas ruang parkir ini akan dibahas mengenai kondisi ruang parkir, karakteristik ruang parkir, serta pemecahan masalah. Pembahasan pada permasalahan ini dimulai dari identifikasi permasalahan di lapangan, studi literatur, survei pendahuluan untuk mengetahui kondisi eksisting dan pengumpulan data. Kemudian dilanjutkan menganalisis data dan pembahasan, sehingga didapatkan kapasitas ruang parkir aktual pada sepeda motor dan mobil. Selanjutnya diterapkan analisis karakteristik menurut Dirjen Perhubungan Darat 1996, lalu ditarik kesimpulan dan saran.Dari hasil survei ini didapatkan karakteristik parkir Ruko Mega Galaxy Surabaya yaitu kapasitas statis kendaraan sebanyak 500 SRP sepeda motor dan 120 SRP mobil. Pada akumulasi parkir maksimum sepeda motor 556 kendaraan dan mobil 138 kendaraan. Volume parkir sepeda motor 1256 kendaraan dan mobil 941 kendaraan. Untuk durasi parkir maksimum sepeda motor 3.69 jam dan mobil 2.07 jam. Turn over parking maksimum sepeda motor sebanyak 3 kali pergantian dan mobil 8 kali pergantian. Indeks parkir maksimum sepeda motor adalah 111% dan mobil 115%. dan kapasitas dinamis sepeda motor sebesar 2300 SRP dan mobil 552 SRP. Berdasarkan kondisi faktual, akumulasi parkir maksimum sudah tidak mampu menampung volume kendaran sehingga jika diproyeksikan dalam 3 tahun kedepan perlu adanya penambahan SRP.Kata Kunci: Karakteristik, SRP, Sepeda Motor, Mobil, Ruko